السياسة الإجتماعية ودورها في تحقيق التنمية المستدامة في الجزائر 2001 إلى 2022 - مسعودي شهرزاد (جامعة المسيلة, 2022)
ينصب إهتمام دراستنا في تبيان أهمية السياسات الإجتماعية كجزء من السياسات العامة للدولة، ودورها في إرساء دعائم العدالة الإجتماعية وإنصاف الفئات الضعيفة مع إحداث التوازن بين مختلف طبقات المجتمع، عاكسة بذلك وجود نظام سياسي يتصف بالديمقراطية التشاركية وفق آلية التخصيص السلطوي للقيم والموارد إذ تعبر السياسات الإجتماعية عن أفعاله وتوجهاته، والتي عبرها يتكفل بتجسيد إستراتيجية التنمية المستدامة المتمثلة في أهدافها بعيدة المدى والمتصلة بشكل علائقي مع السياسات الإجتماعية ضمن إطار العدالة الإجتماعية والإنصاف بشكل إستدامي.كل ذلك تم إسقاطه على دراسة السياسات الإجتماعية في الجزائر بإبراز مساهمتها في تحقيق التنمية المستدامة. الكلمات المفتاحية: السياسة العامة، السياسة الإجتماعية، التنمية المستدامة. Study Title Social policy and its role in achieving sustainable development in Algeria 2001 to 2022 Summary: The interest of our study is to show the importance of social policies as part of the state's general policies, and their role in laying the foundations of social justice and fairness to the weak groups while striking a balance between the various classes of society, reflecting the existence of a political system characterized by participatory democracy in accordance with the mechanism of authoritarian allocation of values and resources as social policies express the His actions and directions, through which he undertakes to embody the sustainable development strategy represented in its long-term goals and related in a relational way with social policies within the framework of social justice and equity in a sustainable manner. All of this was projected on the study of social policies in Algeria by highlighting its contribution to achieving sustainable development. Keywords: public policy, social policy, sustainable development
Keywords: السياسة العامة، السياسة الإجتماعية، التنمية المستدامة